Engagement and Work Readiness of College Students - Magallanes, Celo I. (Technium Social Sciences Journal, 2022)
Students should actively engage in school, acquire work readiness skills or soft skills needed for employment, and be amply ready for jobs. This descriptive, comparative, correlational, and predictive study aimed to assess the relationships between student engagement and work readiness skills of 565 college students at a private university in the Philippines. The demographic variables include sex, work experience, and college enrolled in. This study used the Student Engagement in School Inventory and the Real-World Work Readiness Scale. As a whole and by college unit, sex, and paid work experience, university students were highly engaged in cognitive, affective, and behavioral dimensions. Unlike some university students, COED students were more engaged. Sex differences and paid work experience did not affect students' engagements. Soft skills, namely, motivation, maturity, personal development, organizational awareness, technical focus, interpersonal orientation, positive work attitudes, problem solving, adaptability, and resilience made them work-ready. In most areas, students' soft skills were similar. CIT students appeared less adaptable than other students, while CCJE students were more technically focused. Males are better problem-solvers, but females are more motivated and have higher organizational awareness. Those students with paid work experience had higher technical focus and were better problem-solvers because their work experience has enhanced these specific skills necessary in the workplace. Lastly, there is a strong link between engagement and work readiness, which supports the idea that student engagement enhances work readiness.